Mampuju Mamongo: Makna Simbolik Dalam Proses Lamaran Suku Pamona di Desa Bungapati Kabupaten Luwu Utara - Lisdawati Lisdawati; Abdul Rahman; Najamuddin Najamuddin (Universitas Hamzanwadi, 2026)
This study aims to analyze the meaning of the symbolic message contained in the procession of the Mampuju Mamongo of the Pamona Tribe in Bungapati Village, North Luwu Regency, Mampuju Mamongo procession in the tradition of the Pamona Tribe in Bungapati Village, North Luwu Regency, the position of Mampuju Mamongo in maintaining the sustainability of the Pamona Tribe proposal tradition in Bungapati Village, North Luwu Regency. The researcher uses a qualitative descriptive research type with a phenomenological approach. Data collection techniques through observation, interviews, and documentation. The results of the study show that the meaning of symbolic messages in the traditional elements of proposal packages such as areca nuts, betel leaves, betel lime, tobacco, rattan, coins, and areca nut fronds contain deep philosophical values symbolized by purity, honesty in relationships, responsibility, and unity and harmony between the two families united through customary bonds. The Mampuju Mamongo procession is carried out through structured stages, namely, metukana (asking), mantonge mamongo (wrapping), and mabulere mamongo (opening of packages). Each stage has its own function and meaning that gradually confirms the seriousness and responsibility of the male party in the customary proposal process, as well as providing space for the woman and her family to express their consent, and accept customary and social ties. The sustainability of this tradition is maintained through active value inheritance efforts and collaboration between traditional leaders, village governments, and the younger generation, through traditional documentation and strengthening village customary institutions to maintain the cultural identity of the Pamona Tribe in the midst of modernization.